Ethyl acetate leaf fraction of Cnidoscolus aconitifolius (Mill.) I. M. Johnst: antioxidant potential, inhibitory activities of key enzymes on carbohydrate metabolism, cholinergic, monoaminergic, purinergic, and chemical fingerprinting - Basiru Olaitan Ajiboye (International Journal of Food Properties, 2018)
In this study, the antioxidant, carbohydrate metabolism, cholinergic, monoaminergic, and purinergic enzyme activities of ethyl acetate leaf fraction of Cnidoscolus aconitifolius were evaluated with the high-performance liquid chromatography (HPLC) analysis. The ethyl acetate fraction of the plant leaf was tested for antioxidant properties, key carbohydrate metabolism, cholinergic, monoaminergic, and purinergic enzyme activities using standard procedures, while the chemical composition of the fraction was evaluated using HPLC. The results revealed that the fraction has higher phenolic compounds than flavonoid and exhibited the ability to scavenge iron chelation and ABTS. The fraction also inhibited the activities of α-amylase and α-glucosidase, acetylcholinesterase, butyrylcholinesterase, monoamine oxidase, tyrosinase, arginase, Ecto-5’-nucleotidase, phosphodieterase-5, angiotensin-I-converting enzyme and encouraged the activity of Na+/K+-ATPase. The HPLC analysis revealed that the ethyl acetate fraction contained coumaric acid, amentoflavone, hesperidin, protocatechuic acid, kaempferol, dihydromyricetin, quercetin,and rutin. The obtained results in this study suggest that the ethyl acetate fraction obtained from aqueous extracts of Cnidoscolus aconitifolius leaf possessed outstanding antioxidative potentials. Thus, excellent enzyme inhibitory activities probably due to bioactive compounds are also observed in the leaf.